Proyecto de intervención, restauración y conservación del Templo de la Merced en Morelia, Michoacán - Cruz Cardoso, Salomón Oscar (Universidad Michoacana de San Nicolas de Hidalgo, 2020)
The relevance of the Restoration of the Architectural Heritage is the product of continuous efforts on the part of many actors in society, both nationally and internationally. It is important to safeguard our inherited heritage since it accounts for the historical past and has the burden of symbolism that unifies us as a society and represents us as humanity. With the passage of time there is the evolution of materials and construction techniques, which are not better because they are new, but have brought with them the forgetfulness and evolution of old construction techniques. For this reason it is obligatory to know and study them especially for the achievement of the end of Conservation and Restoration of said inherited heritage. The Temple of La Merced and its ex-Convent in Morelia, Michoacán, is an architectural object of incalculable values, built in the late seventeenth century. Made of stonework with quarry, now apparent, it is a material that gives an urban image to the city of Morelia, which in together with its urban context, they constitute today the Historical Center which was declared a Cultural Heritage of Humanity by UNESCO since 1991. The research of this work presents a methodology of intervention to the historical and cultural heritage, where it´s state of conservation is evaluated and diagnosed to improve a project of restoration and comprehensive adaptation project is determined, governed mostly by qualitative methods: with historical research and architectural prospecting; as well as quantitative methods: with the creation of numerical models of mathematical analysis to generate the state of the structural system and environmental analysis with environmental data. Both considered essential to jointly formulate a good intervention judgment. The general concept that governs the research is that of comprehensive transdisciplinary intervention.

La relevancia de la Restauración del Patrimonio Arquitectónico es producto de esfuerzos continuos de parte de muchos actores de la sociedad, tanto nacionalmente como internacionalmente. Es importante salvaguardar nuestro patrimonio heredado dado que da cuenta del pasado histórico y posee carga del simbolismo que nos unifica como sociedad y nos representa como humanidad. Con el paso del tiempo existe la evolución de materiales y técnicas constructivas, que no por ser nuevas son mejores, pero ha traído consigo el olvido y evolución de las técnicas constructivas antiguas. Por ello es obligado conocerlas y estudiarlas especialmente para el logro del fin de la Conservación y Restauración de dicho patrimonio heredado. El Templo de la Merced y su ex Convento de Morelia, Michoacán, es un objeto arquitectónico de valores incalculables, construido a finales del siglo XVII. Hecho de cantería, ahora aparente, es un material que le da imagen urbana a la ciudad de Morelia, que, en conjunto con su contexto urbano, constituyen hoy día el Centro Histórico el cual fue declarado Patrimonio Cultural de la Humanidad por la UNESCO desde 1991. La investigación de este trabajo presenta una metodología de intervención al patrimonio histórico y cultural, donde se evalúa y diagnostica su estado de conservación y, se determina un proyecto de restauración y adecuación integral, regido en su mayoría, tanto por métodos cualitativos: con investigación histórica y prospección arquitectónica; así como métodos cuantitativos: con creación de modelos numéricos de análisis matemáticos para generar el estado del sistema estructural y el análisis ambiental con datos medioambientales. Considerados ambos primordiales para formular conjuntamente un buen juicio de intervención. El concepto general que rige la investigación es el de la intervención integral transdisciplinar.
Facultad de Arquitectura. Especialidad en Restauración de Sitios y Monumentos
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3229; info:eu-repo/classification/cti/4; FA-E-2020-1309; Cal; Cantería; Caliza